2014
DOI: 10.1007/s10661-014-3670-4
|View full text |Cite
|
Sign up to set email alerts
|

Relative Phytoplankton growth responses to physically and chemically dispersed South Louisiana sweet crude oil

Abstract: We conducted controlled laboratory exposure experiments to assess the toxic effects of water-accommodated fractions (WAFs) of South Louisiana sweet crude oil on five phytoplankton species isolated from the Gulf of Mexico. Experiments were conducted with individual and combinations of the five phytoplankton species to determine growth inhibitions to eight total petroleum hydrocarbon (TPH) equivalent concentrations ranging from 461 to 7,205 ppb. The composition and concentration of crude oil were altered by phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 23 publications
3
28
1
Order By: Relevance
“…The mechanisms by which low concentrations of oil enhance phytoplankton growth are unclear, but enhancements of growth or photosynthetic rates similar to the effects we observed (Figure 1) have been reported in several other studies [13,15,19,23,29,31,57]. The positive effects may be indirect and involve interactions with into lipids or other components of the cell in sufficient concentrations to upset normal metabolic functions.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…The mechanisms by which low concentrations of oil enhance phytoplankton growth are unclear, but enhancements of growth or photosynthetic rates similar to the effects we observed (Figure 1) have been reported in several other studies [13,15,19,23,29,31,57]. The positive effects may be indirect and involve interactions with into lipids or other components of the cell in sufficient concentrations to upset normal metabolic functions.…”
Section: Discussionsupporting
confidence: 81%
“…A number of previous investigators have reported stimulatory effects of oil on phytoplankton growth or photosynthesis at low oil concentrations, typically less than 1 mg L -1 , and inhibition at high oil concentrations [13,15,19,23,[29][30][31]. The toxicity of crude oil to phytoplankton results from a variety of effects that reflect the complex composition of crude oil.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations